KONSEP PENCIPTAAN PEREMPUAN PERTAMA DALAM AL-QUR’AN - Nurhidayah; Siti Fadila; Ali Akbar (PT. Hasba Edukasi Mandiri, 2026)
This study examines the concept of the creation of the first woman in the Qur'an through an analysis of verses related to the origin of human creation, particularly Surah An-Nisa [4]: 1, Surah Al-A'raf [7]: 189, and Surah Az-Zumar [39]: 6. The objective of this research is to understand how the Qur'an describes the creation of women and to explore the interpretations of classical and contemporary Qur'anic commentators regarding these verses. This research employs a qualitative approach using the library research method, drawing upon the Qur'an, tafsir literature, hadith collections, and relevant scholarly works. The data were analyzed using content analysis and comparative analysis of various exegetical perspectives. The findings reveal that the Qur'an emphasizes the unity of human origin through the concept of nafs wahidah (a single soul), which serves as the foundation for equality between men and women. Differences in interpretation arise concerning the phrase wa khalaqa minha zaujaha, where some commentators interpret it literally as Eve being created from Adam’s rib, while others understand it metaphorically as being created from the same human essence. This study concludes that the primary message of the Qur'an regarding the creation of women is the affirmation of human unity, respect for women, and the importance of harmonious relationships between men and women in human life.